International BioLaw - Bernal-Camargo, Diana Rocío (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This article presents an approach to the BioLaw and its special reference to the international field, where even though the regulations, there is a challenge of great dimension to the own international system and domestic legislation. A first reference to bioethics and its principles is made, as in this context comes into play the BioLaw and focuses on some regulations that specially provide principles that lead the resolution of bioethical and biojuridical problems.